Mediation effect of organizational culture on the relationship between perceived ethics and SMEs performance - Abdullahi Hassan Gorondutse; Haim Hilman Abdullah (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: This research aims to examine the association between perceived ethics and SMEs performance; also determine the mediation effect of organizational culture on the relationship. Design/methodology/approach: Based on the literature review, this research developed a conceptual model of Perceived ethics, organizational culture and performance. This research applied purposive sampling to gather data from owners/managers of SMEs in Kano State North-West of Nigeria. Apart from assessing the reliability and validity of the constructs through confirmatory factor analysis, this research also used Partial Least Square Techniques (PLS) of analysis approach to test the proposed hypothesis. Findings: Statistical result reveals that the relationship between perceived ethics and SMEs performance was found to be significant at p.value less than 0.001. Similarly as postulated the organizational culture mediates the relationships with significant value. Research limitations/implications: The sample for this study is based on SMEs and cross sectional in nature, In addition, the present study employed quantitative techniques future study can employed qualitative or case study method for design and analysis of information. Practical implications: The finding of this study can assist practitioners and policy makers in SMEs to support the idea of social responsibility in designing strategic plan for superior performance. As whole, the outcome of this research will assist managers for better understanding of the business social responsibility antecedents under the perspective SMEs. Originality/value: This paper has tried to provide a comprehensive understanding about business social responsibility antecedents under the perspective SMEs context in Nigeria. Since there was a lack of such research in SMEs context, this research can provide theoretical contribution and managerial basis for future researches as well as implications for the managers.
Keywords: 650; perceived ethics; organizational culture; SMEs performance and Nigeria